Apoptosis in chronic myeloid leukemia cells transiently treated with imatinib or dasatinib is caused by residual BCR-ABL kinase inhibition - Simara, Pavel; Stejskal, Stanislav; Koutna, Irena; Potesil, David; Tesarova, Lenka; Potesilova, Michaela; Zdrahal, Zbynek; Mayer, Jiri (American journal of hematology, 2013)
Transient, potent BCR-ABL inhibition with tyrosine kinase inhibitors (TKIs) was recently demonstrated to be sufficient to commit chronic myeloid leukemia (CML) cells to apoptosis irreversibly. This mechanism explains the clinical efficacy of once-daily dasatinib treatment, despite the rapid clearance of the drug from the plasma. However, our in vitro data suggest that apoptosis induction after transient TKI treatment, observed in the BCR-ABL-positive cell lines K562, KYO-1, and LAMA-84 and progenitor cells from chronic phase CML patients, is instead caused by a residual kinase inhibition that persists in the cells as a consequence of intracellular drug retention. High intracellular concentrations of imatinib and dasatinib residues were measured in transiently treated cells. Furthermore, the apoptosis induced by residual imatinib or dasatinib from transient treatment could be rescued by washing out the intracellularly retained drugs. The residual kinase inhibition was also undetectable by the phospho-CRKL assay. These findings confirm that continuous target inhibition is required for the optimal efficacy of kinase inhibitors.
Keywords: thiazoly; Apoptosis; chronická fáze myeloidní leukemie; adaptorové proteiny signální transdukční; Bone Marrow Cells; Phosphorylation; Osmolar Concentration; benzamidy; apoptóza; Neoplastic Stem Cells; nádorové buněčné linie; Protein Processing, Post-Translational; Benzamides; jaderné proteiny; protinádorové látky; Adaptor Proteins, Signal Transducing; osmolární koncentrace; biologický transport; piperaziny; pyrimidiny; Fusion Proteins, bcr-abl; Kinetics; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Antineoplastic Agents; Leukemia, Myeloid, Chronic-Phase; Thiazoles; inhibitory proteinkinas; nádorové kmenové buňky; Tumor Cells, Cultured; Biological Transport; kinetika; Piperazines; Pyrimidines; chronická myeloidní leukemie; posttranslační úpravy proteinů; Cell Line, Tumor; Protein Kinase Inhibitors; Nuclear Proteins; fosforylace; nádorové buňky kultivované; buňky kostní dřeně; bcr-abl fúzní proteiny; lidé; Humans